Comparative study of primary productivity in cage culture unit and fish pond in relation to different levels of water depth - Sharma, Pawan Kumar; Kumar, J. Stephen Sampath; Senthil Kumar, V. (Journal of the Inland Fisheries Society of India, 2021)
Primary productivity describes the rate of energy conversion by photosynthetic and chemosynthetic autotrophs in the form of organic substances. The present study assessed the effect of water depth on gross primary productivity (GPP), net primary productivity (NPP) and community respiration (CR) in fish cage and fish pond as well as found out the effect of water depth on pH and temperature. Maximum GPP levels were observed at 20 cm water depth in fish pond (0.74±0.03 gC m-3h-1) and cage (0.41±0.01 gC m-3h- 1) respectively. Minimum GPP values were observed at 60 cm water depth in pond (0.37±0.02 gC m-3h-1) and cage (0.31±0.06 gC m-3h-1) respectively. The maximum value of CR was found at 20 cm depth while minimum value was observed at 40 cm depth in the pond water. The range of values of pH was 8.73 ±0.26 to 8.89±0.26 in cage while in pond it was 8.47± 0.31 to 8.76± 0.26. The range of temperature in the cage was 33.45 ±0.36 to 33.67 ± 0.26 oC while in the pond it was 33.66 ±0.32 to 33.86 ± 0.21 oC. The study revealed that GPP is inversely proportional to the water depth both in cage and pond. The GPP and CR were higher in the pond than in cage at every depth, resulting in lower NPP in the pond than cage. Key words Net primary productivity, Gross primary productivity, Community respiration, Water depth